RNA processing in auxin and cytokinin pathways - Hrtyan, Mónika; Šliková, Eva; Hejátko, Jan; Růžička, Kamil (Journal of experimental botany, 2015)
Auxin and cytokinin belong to the 'magnificent seven' plant hormones, having tightly interconnected pathways leading to common as well as opposing effects on plant morphogenesis. Tremendous progress in the past years has yielded a broad understanding of their signalling, metabolism, regulatory pathways, transcriptional networks, and signalling cross-talk. One of the rapidly expanding areas of auxin and cytokinin research concerns their RNA regulatory networks. This review summarizes current knowledge about post-transcriptional gene silencing, the role of non-coding RNAs, the regulation of translation, and alternative splicing of auxin- and cytokinin-related genes. In addition, the role of tRNA-bound cytokinins is also discussed. We highlight the most recent publications dealing with this topic and underline the role of RNA processing in auxin- and cytokinin-mediated growth and development.
Keywords: kyseliny indoloctové; Cytokinins; alternativní sestřih; cytokinin; miRNA; RNA processing; non-coding RNA; Plant Development; Plant Growth Regulators; Auxin; gene silencing; vývoj rostlin; nekódující RNA; regulace genové exprese u rostlin; splicing; Alternative Splicing; Gene Expression Regulation, Plant; RNA, Untranslated; regulátory růstu rostlin; tRNA.; RNA Interference; Indoleacetic Acids; RNA interference; cytokininy